Integrating Islamic Values into Character Education: A Multidisciplinary Approach to Preventing Moral Degradation among Youth - Prasetio Utomo (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
This study explores how Islamic values can be integrated into character education to prevent moral decline among youth in the era of globalization and technological change. The research responds to growing concerns about dishonesty, intolerance, lack of discipline, and weak social responsibility among younger generations. Using a qualitative descriptive approach, data were gathered through interviews, observations, and document analysis in Islamic-based schools. Results show that students’ perception of Islamic value integration in character education is high (M = 4.27). Spiritual values scored the highest (M = 4.34), followed by moral discipline (M = 4.29), social responsibility (M = 4.21), and intellectual integrity (M = 4.17). Regression analysis indicates that Islamic values significantly enhance the effectiveness of character education, explaining 54% of the variance. Spiritual values had the strongest effect, while moral discipline, social responsibility, and intellectual integrity also made meaningful contributions. The findings suggest that integrating Islamic principles supports students’ spiritual, moral, social, and intellectual growth, making them both academically competent and ethically responsible. This integration offers a practical response to the challenges of Society 5.0, balancing modern skills with strong moral foundations.